Musical Characteristics of Mangkla Band Lamduan Waisai Kho Rum District Pichai Subdistrict Uttaradit Province - Tup-at, Teerapong; Nakpee, Prateep (Rangsit Music Journal, 2024)
This research aimed to study History Music characteristics and roles and duties of the Lamduan Waisai Mangkala Band, Khorum Sub-district, Pichai District, Uttaradit Province. The study was conducted using document and field study methods with observation and interviews from experts, faculty heads, senior musicians, musicians, employers and audiences. The results of the thesis study were presented through descriptive and analytical methods. The reports of the results are as follows. 1) In an aspect of history, it was that there are 3 generations of succession by Mr. Petch Sangarun, the leader of Band 1 has been transmitted to Mr. Boonlue Khamthong, the leader of the band’s second generation and Mr. Prayad Kaew Phum Na Wong. At present, the third generation has received position. 2) In terms of musical characteristics 2.1) In the composite field, the Band is composed of Pi nae, mangkala drum, standing drum, haunted drum, gong, mong, krub, cymbal, cymbals, and cymbals. 2.2) In terms of rhythm and speed the 2/4 is used 2.3) In terms of melody, the scale of B flat major is used 2.4) In the field of concerto for musical instruments, the Band is an accompaniment. 3) Regarding the form, it is a short, easy-to-remember song with a single song that is used to play with fresh Pi Nae. 3) In terms of roles and functions, it was found that the Band is used to lead the parade in various auspicious events and were able to adapt to the changing social conditions. traditions and rituals results from interaction cultural and social.